PEMBERDAYAAN KELOMPOK TANI DESA SAMBIREJO MELALUI PENGOLAHAN SAMPAH TERPADU GUNA PENYEDIAAN ENERGI ALTERNATIF DAN PENINGKATAN PENDAPATAN KELUARGA - Lusiana Lusiana; Evi Maryanti; Ulfasari Rafflesia (Universitas Bengkulu, 2018)
Community services activity group on empowerment of farmers group in sambirejo trhrouh integrated process of waste to energy alternative and improvement of family income have been done. This activity aims to improve the welfare of the villagers in sambirejo especially members of Amanah Farmer Group and Makmur Jaya Farmer Group through community based integrated waste. In this activity, training of garbage separation of organic and inorganic, making organic fertilizer/compost with Takakura method, making handicrafts from plastic packaging waste and biogas installation which is expected to produce alternative energy to replace LPG and firewood for daily cooking. The implementation of these activities carried out by two methods : (1) counseling and discussion about separating domestic waste, products can be made from waste, and what types of waste can be used, (2) demonstration and practice on how to make compost with Takakura method, and biogas installations on both partners. Through these activities are expected to members of the two groups of farmers, especially the women will be able to sort household waste properly and process the waste into products which has economic value that can create small-scale domestic industry that would be able to contribute to the family and the environment. Keywords: Farmer’s Group, Waste, Takakura, Plastic Pack, Economic Product